RESPONSE OF THE QUR'AN TO THE TRANSGENDER PHENOMENON STUDY OF MAQASHIDI'S INTERPRETATION - Aswindasari, Aliffia; Marhamah, M (QiST: Journal of Quran and Tafseer Studies, 2024)
This article discusses one of the issues of LGBT, namely transgender, which is now widespread and can be found in many places. Transgender is someone who changes or switches gender from their original gender. This transgender phenomenon is considered deviant because it changes what God has created and violates His nature. The purpose of this paper is to find out the arguments and interpetations regarding this transgender phenomenon by using analysis of maqāṣidi interpretation studies initiates by Abdul Mustaqim and using library research by analyzing Al-Qur’an surat An-Nisa verse 119 and ar-Rum verse 30. There are many reasons for the prohibition of this transgender behavior, interpreters say that transgender phenomenon has violated human nature. By using maqāṣidi interpretation, the prohibition is not only based on the meaning if the text, but if reviewed from the maqashidi, the wisdom of this transgender phenomenon will be found, namely hifz al-din, hifz al-nasl, hifz al-nafs, hifz al-‘aql, dan hifz al-daulah.